Structural diversity in manganese, iron and cobalt complexes of the ditopic 1,2- bis(2,2’-bipyridyl-6-yl)ethyne ligand and observation of epoxidation and catalase activity of manganese compounds - Madhu, Vedichi; Ekambaram, Balaraman; Shimon, Linda J. W.; Diskin, Yael; Leitus, Gregory; Neumann, Ronny (Royal Society of Chemistry, 2010)
A ditopic 1,2-bis(2,2′-bipyridyl-6-yl)ethyne ligand, L, has been synthesized for the first time by consecutive Suzuki and Sonogashira coupling reactions either in a one- or two-step synthesis. Coordination of L with some first-row transition metals, Fe, Mn and Co showed a very rich structural diversity that can be obtained with this ligand. Reaction of L with MnII(OAc)2 yielded a dimanganese(II) complex, [Mn2L(μ-OAc)3]PF6, (1) where the two somewhat inequivalent trigonal-bipyramidal Mn atoms separated by 3.381 Å are bridged by L and three acetate moieties. A similar reaction of L with MnIII(OAc)3 yielded a very different dimanganese complex [Mn2L′(OH)(OAc)2(DMF)2]PF6·DMF (2) where L′ is a E-1,2-bis(2,2′-bipyridyl-6-yl)ethene fragment that was formed in situ. The L′ ligand bridges between the two Mn centers, despite its trans configuration, which leads to a very strained ethene bridging moiety. The Mn atoms are also bridged by two acetate ligands and a hydroxy group that bridges between the Mn atoms and the ethene fragment; DMF completes the octahedral coordination around each Mn atom which are separated by 3.351 Å. A comproportionation reaction of L with MnII(OAc)2 and n-Bu4NMnO4 yielded a tetramanganese compound, [Mn4(μ3-O)2(OAc)4(H2O)2L2](PF6)2·2CH3CN (3). Compound 3 has a dimer of dimers structure of the tetranuclear Mn core that consists of binuclear [Mn2O(OAc)2L]+ fragment and a PF6 anion. BVS calculations indicate that 3 is a mixed-valent 2MnII plus 2MnIII compound where two [MnII2O(OAc)2L]+ fragments are held together by MnIII–O inter-fragment linkers which have a distorted octahedral geometry. The Mn atoms in the [Mn2O(OAc)2L]+ fragments have a capped square-pyramid configuration where an aqua ligand is capped on one of the faces. Although the aqua ligand is well within a bonding distance to a carbon atom of the proximal ethyne bridge, there does not appear to be an oxygen–carbon bond formation, rather the ligand is constrained in this position, as deduced by the observation that the bond lengths and angles of the ligand are essentially the same as those for the free ligand, L. Reaction of L with perchlorate or triflate salts of Fe(II), Mn(II) and Co(II) in dry acetonitrile yielded binuclear triple helicate structures (2[thin space (1/6-em)]:[thin space (1/6-em)]3 metal to L ratios) [Fe2L3](CF3SO3)4·CH3CN (4), [Mn2L3](ClO4)4·1.7CH3CN·1.65EtOEt (5) and [Co2L3](ClO4)4·2CH3CN·2EtOEt (6) where each M(II) center with a slightly distorted octahedral geometry is bridged by three of the ditopic ligands. The M–M distances varied; 5.961 Å (Mn), 6.233 Å (Co) 6.331 Å (Fe). Reaction of L with Co(ClO4)2·6H2O in wet acetonitrile yielded a dicobalto(III) compound, [Co2L′3(O)2](ClO4)2·H2O (7), with two types of L′ fragments; one bridging between the two Co centers and two non-bridging ligands, each bonded to a Co atom via one bipyridyl group where the other is non-bonding. The octahedral coordination sphere around each Co atom is completed by the formation of a cobalt–carbon bond from the two carbon atoms of the ethene moiety of the bridging ligand and by a hydroxy moiety that is also bonded to the ethene group of the non-bridging ligand. Reaction of L with Co(ClO4)2·6H2O in dry acetonitrile in the presence of Et3N yielded the tetracobalto(II) complex {[Co2L4(OH)4](ClO4)4}2 (8) with a unique twisted square configuration of cobalt ions with Co–Co distances of 3.938 to 4.131 Å. In addition to the L bridging ligand the Co atoms are linked by hydroxy moieties. Some preliminary catalytic studies showed that the Mn compounds 1 and 2 were active (high yield within 3 min) for alkene epoxidation with peracetic acid and hydrogen peroxide dismutation (catalase activity).

Photocatalytic splitting of CS2 to a carbon-sulfur polymer and S8 catalyzed by a bimetallic ruthenium(II) compound with a tertiary amine binding site - towards photocatalytic splitting of CO2? - Livanov, Konstantin; Madhu, Vedichi; Balaraman, Ekambaram; Shimon, Linda J. W.; Diskin-Posner, Yael; Neumann, Ronny (Inorganic Chemistry, 2011)
The catalytic photocleavage of CS2 to S8 and a (CxSy)n polymer with visible light using a dinuclear ruthenium(II) compound with a bipyridine units for photoactivity and a vicinal tertiary amine binding site for CS2 activation was studied. The catalyst was characterized by X-ray diffraction, 1H NMR, and 13C NMR, ESI-MS and elemental analysis. CS2 photocleavage was significant (240 turnovers, 20 h) to yield isolable S8 and a (CxSy)n polymer. A mononuclear catalyst or one without an amine binding site showed significantly less activity. XPS of the (CxSy)n polymer showed a carbon/sulfur ratio ∼1.5–1.6 indicating that in part both C–S bonds of CS2 had been cleaved. Catalyst was also included within the polymer. The absence of peaks in the 1H NMR verified the (CxSy)n nature of the polymer, while 13C NMR and IR indicated that the polymer had multiple types of C–S and C–C bonds.

Sodium periodate mediated oxidative transformations in organic synthesis - Sudalai, Arumugam; Khenkin, Alexander; Neumann, Ronny (Organic & Biomolecular Chemistry, 2015)
The investigation of new oxidative transformations for the synthesis of carbon-heteroatom and heteroatom-heteroatom bonds is of fundamental importance in the synthesis of numerous bioactive molecules and fine chemicals. In this context, NaIO4, an exciting reagent, has attracted increasing attention enabling the development of these unprecedented oxidative transformations that are difficult to achieve otherwise. Thus, NaIO4 has been successfully explored as a versatile oxidant for a variety of fundamental organic transformations such as C-H activation, oxidative functionalization of alkenes and other interesting oxidative transformations and its application in the synthesis of bioactive natural products. This review summarizes recent developments in this area with NaIO4 as a versatile oxidant and brings out many challenges that still remain elusive for the future.